NMR and Metabolomics—A Roadmap for the Future - David S. Wishart; Leo L. Cheng; Valérie Copié; Arthur S. Edison; Hamid R. Eghbalnia; Jeffrey C. Hoch; Goncalo J. Gouveia; Wimal Pathmasiri; Robert Powers; Tracey B. Schock; Lloyd W. Sumner; Mario Uchimiya (Metabolites, 2022)
Metabolomics investigates global metabolic alterations associated with chemical, biological, physiological, or pathological processes. These metabolic changes are measured with various analytical platforms including liquid chromatography-mass spectrometry (LC-MS), gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance spectroscopy (NMR). While LC-MS methods are becoming increasingly popular in the field of metabolomics (accounting for more than 70% of published metabolomics studies to date), there are considerable benefits and advantages to NMR-based methods for metabolomic studies. In fact, according to PubMed, more than 926 papers on NMR-based metabolomics were published in 2021—the most ever published in a given year. This suggests that NMR-based metabolomics continues to grow and has plenty to offer to the scientific community. This perspective outlines the growing applications of NMR in metabolomics, highlights several recent advances in NMR technologies for metabolomics, and provides a roadmap for future advancements.